Online Diagnostics and Optimization of Photovoltaic Panel Arrays for Enhanced System Efficiency - Lagra Mohammed; Belmessaoud Larbi; Fathiza Ali Younes; Kraiem Bachir (University of Shahid Hama Lakhdar - El Oued, 2025)
This master's project aims to design an online diagnostic and optimization platform for photovoltaic (PV) panel systems using Internet of Things (IoT) technology. The idea stemmed from observed challenges in monitoring performance and ensuring the efficiency of PV systems. These challenges include energy losses due to partial shading, dirt accumulation, undetected faults, and the lack of real-time system feedback. The project seeks to enhance overall system efficiency through real-time fault detection and performance analysis using IoT-based monitoring. This helps reduce downtime, improves maintenance scheduling, and ensures stable energy output, especially in remote or large-scale installations. The project is divided into two main parts: hardware and software. On the hardware side, sensors for voltage, current, irradiance, and temperature were deployed across the PV array. A custom PCB was designed to process and wirelessly transmit the data. On the software side, a cloud-based platform was developed to analyze the data, along with an Android application to display performance metrics and send alerts in case of anomalies. Optimization algorithms such as Maximum Power Point Tracking (MPPT) and intelligent cleaning suggestions were implemented to boost performance. The system was tested on a small-scale PV installation, where it successfully identified faults and optimized power output, aligning with the project's core objectives. يُقد م هذا العمل ح ل تقني ا متقد ما لمراقب ة وتشخيص أداء الألواح الشمسي ة في محطات الطاق ة الكهروضوئي ة واسعة النطاق، حيث تتوزع آلاف الألواح على مساحات كبيرة، ما يزي د م ن احتمالي ة حدوث أعطال تؤثر على كفاءة النظا م ككل، مثل الغبار، التظليل، وتقلبات الطقس، إضاف ة إلى التوصيلت الضعيف ة يعتمد النظام المصم م على بني ة " slave - master " موزعة، حيث تقوم وحدات محلية (slave) بجمع بيانات الجهد والتيار بشك ل لحظي وترسلها لاسلكي ا إلى وحدة مركزي ة (master) ، تقوم بدورها بتحليل البيانات، عرضها، وتنفيذ أوامر تحكم تلقائي ة مث ل عزل اللوح المتعط ل مع التركيز على خفض استهلك الطاق ة وتقلي ل EasyEDA تم تطوير المنصة الإلكتروني ة للجهاز باستخدام بيئ ة التداخل الكهرومغناطيسي، كما تم اعتماد تصميم معيار ي يسهل صيانت ه وتطويره مستقب ل . من أبرز خصائص هذا النظا م الذكي دعم ه لبروتوكول إعادة تشكيل مصفوفات الألواح الكهروضوئية، والذي يُعي د توجيه التيار حول الألواح المتعطلة، مما يحس ن م ن موثوقي ة النظا م ويقلل م ن الخسائر الناتج ة ع ن الأعطال ما يتيح مراقب ة مستمرة، تحلي ل ذكي ا للأداء، وتشغي ل مرن ا (IoT) يعتمد النظام أي ضا على تقنيات إنترنت الأشياء في حالات ضعف أو انقطاع الاتصا ل بالشبك ة . يُساهم هذ ا التكام ل في رفع كفاءة الطاق ة وتحقيق أقصى استفادة ممكن ة من النظام في مختلف الظروف البيئي ة والتشغيلية
Master's thesis in electromechanics.2025
Keywords: Photovoltaic Systems; Online Diagnostics; IoT Monitoring; AC/DC Voltage and Current Sensors; Maximum Power Point Tracking (MPPT); Renewable Energy Optimization; الطاق ة الشمسية، الألواح الكهروضوئية، المراقب ة الذكية، التشخيص الفوري، النظام الموزع، إعادة تشكيل المصفوفات، إنترنت الأشياء، كفاءة الطاقة، التحك م الذاتي، EasyEDA